Luminescent early-late-hetero-tetranuclear group IV – Au(i) bisamidinate complexes. Issue 27 (1st July 2022) - Uhlmann, Cedric; Feuerstein, Thomas J.; Seifert, Tim P.; Jung, André P.; Gamer, Michael T.; Köppe, Ralf; Lebedkin, Sergei; Kappes, Manfred M.; Roesky, Peter W.
Abstract : Reaction of the ethynyl compound [HC}CC(NDipp)2 2 Au2 ] with n -BuLi followed by Cp2 MCl2 (M = Ti, Zr) leads to two group IV – gold(i ) heterobimetallic complexes with different photoluminescence properties. Abstract : The versatile metalloligand [HC}CC(NDipp)2 2 Au2 ] (dipp = 2, 6-diisopropylphenyl) was converted into early-late heterotetrametallic complexes [ClCp2 MC}CC(NDipp)2 2 Au2 ] (M = Ti, Zr). These compounds show photoluminescence with either remarkably different (Ti) or similar (Zr) features as compared to related solely coinage metal containing acetylide amidinate complexes.